[INVITED] Electrophoretic plasmonic nanopore biochip genome sequencer. (January 2019) - Mendoza, Edgar A.; Neumann, Alexander; Kuznetsova, Yuliya; Brueck, Steve R.J.; Edwards, Jeremy
Highlights: Self-assembly fabrication of nano-fluidic channels with nanopore "trapping" barriers and roof. Electrophoretic control translocation of "stretched" DNA molecules through nanopore barriers. Raman measurement of DNA nucleobase spectra within nanopore barriers and roof. Abstract: Our research group is investigating a novel DNA sequencing methodology based on an electrophoretic plasmonic nanopore (EPIGeneS) biochip system used to control the translocation rate of DNA molecules through a fractal array of plasmonic nanopores to enable massively parallel optical recognition DNA sequencing. The EPIGeneS biochip uses nanofluidic conduits to transport geometrically-conformed DNA single molecules though a fractal nanopore "trapping" barrier structure composed of silica nanoparticles positioned within the fluid delivery path of the chip's nanofluidic channels. Electrophoretic transport of the DNA molecules through the barrier's nanometer-scaled pores enables the translocation control of DNA single molecules facilitating the Raman spectroscopy detection and measurement of the DNA bases' spectral signatures as they traverse within the fractal-dimensionality nanopore barrier structures. To enhance the spectroscopy detection and measurement of the DNA nucleobase signatures, the EPIGeneS biochip uses plasmonic structures by coating the surface of the barrier silica nanoparticles with metallic layers to enable the use of surface enhanced Raman spectroscopy imaging detection techniques. This paper describes preliminary results obtained by our group for the development and usage of the EPIGeneS biochip platform for the investigation of the DNA translocation control through silica nanopore barrier structures, and the Raman spectroscopy read-out of DNA base signatures during electrophoretic transport through the fractal nanopore barrier structures.